A more perfect union holistic worldviews and the transformation of American culture after World War II - Wood, Linda Sargent (Oxford University Press, 2010)
Linda Sargent Wood book uncovers a holistic sensibility in post-World War II American culture that both tested the logic of the Cold War & fed some of the twentieth century's most powerful social movements, from civil rights to environmentalism to the counterculture.